1992
DOI: 10.1002/hep.1840150212
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced prolonged cholestasis in adults: A histological semiquantitative study demonstrating progressive ductopenia

Abstract: Drug-induced acute hepatitis may be followed by prolonged cholestasis despite the withdrawal of the drug. Eight patients suffering from prolonged cholestasis caused by several drugs were investigated with sequential liver biopsies. At the early stage, lesions of acute cholangitis were observed in most patients; at the chronic phase, ductopenia, defined by the absence of interlobular bile ducts in at least 50% of small portal tracts, was demonstrated in all patients. Ductopenia might be the consequence of acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
84
2
6

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(92 citation statements)
references
References 17 publications
0
84
2
6
Order By: Relevance
“…29 Our results did not support suggested associations with various infections or immunizations. 8 The associations between PBC and various drugs, particularly phenothiazines, suggested by case reports and case series were not confirmed by our results, [12][13][14] although the numbers were very small.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…29 Our results did not support suggested associations with various infections or immunizations. 8 The associations between PBC and various drugs, particularly phenothiazines, suggested by case reports and case series were not confirmed by our results, [12][13][14] although the numbers were very small.…”
Section: Discussioncontrasting
confidence: 86%
“…11 Treatment with various drugs including chlorpromazine, prochlorperazine, and estrogens has also been linked anecdotally with PBC. [12][13][14] Our observation of a large series of PBC patients and published associations with similar diseases suggested that recent surgeries and lifestyle factors, such as smoking, drinking, stressful life events, and pet ownership, would also be worth exploring. Other etiological factors for PBC have been suggested, but we concentrated on those that could be investigated by a self-completion questionnaire.…”
mentioning
confidence: 99%
“…Proliferation of bile ducts in the portal tracts with metaplasia of hepatocytes may have improved bile flow. This phenomenon was also described in drug-induced prolonged cholestasis with ductopenia [11] . However, posttraumatic SC progresses in spite of decreasing bilirubin levels.…”
Section: Follow-up Treatment and Complicationsmentioning
confidence: 59%
“…Patients reported complete recovery from prolonged amoxicillin/clavulanate-induced cholestasis did not have fibrosis on liver biopsy [2,[11][12][13][14] . By contrast, in Degott's review of drug-induced cholestasis, all patients with persistent cholestasis had moderate to severe fibrosis [15] . Given the small number of patients reported with drug-induced vanishing bile duct syndrome and the unpredictability of its occurrence, there have been no clinical trials of treatment regimens.…”
Section: Discussionmentioning
confidence: 90%